(untitled) (Scottish Historical and Archaeological Internet Reports, 2021)
Headland Archaeology (UK) Ltd was commissioned by Axiom Project Services to undertake an archaeological excavation in advance of a commercial development at Thainstone Business Park, Aberdeenshire (NGR: NJ 7707 1809). Excavation identified the remains of a Middle Bronze Age roundhouse and a contemporary urned cremation cemetery. Evidence of Late Bronze Age cremation practices was also identified. A large roundhouse and souterrain dominated the site in the 1st or 2nd century AD. Material culture associated with the Iron Age structures suggested a degree of status to the occupation there.